Lipid droplets are versatile organelles involved in plant development and plant response to environmental changes - Bouchnak, Imen; Coulon, Denis; Salis, Vincent; D’Andréa, Sabine; Bréhélin, Claire (Frontiers in Plant Science, 2023)
Since decades plant lipid droplets (LDs) are described as storage organelles accumulated in seeds to provide energy for seedling growth after germination. Indeed, LDs are the site of accumulation for neutral lipids, predominantly triacylglycerols (TAGs), one of the most energy-dense molecules, and in a much lesser degree, sterol esters. Such organelles are present in the whole plant kingdom, from microalgae to perennial trees, and can probably be found in all plant tissues. Several studies over the past decade have revealed that LDs are not merely simple energy storage compartments, but also dynamic structures involved in diverse cellular processes like membrane remodeling, regulation of energy homeostasis and stress responses. In this review, we aim to highlight the functions of LDs in plant development and response to environmental changes as well. In particular, we tackle the fate and roles of LDs during the plant post-stress recovery phase.